One Aspect of the Evolution of Saline Lakes in the Dry Valleys of South Victoria Land, Antarctica (Extended Abstract) - Nakaya, Shyu; Motoori, Yasuharu; Nishimura, Masakichi (1979)
P(論文) departmental bulletin paper